2022
DOI: 10.1155/2022/7879633
|View full text |Cite|
|
Sign up to set email alerts
|

Application Effect of External and Internal Elevation of Maxillary Sinus in Implant Restoration of Posterior Maxilla

Abstract: Objective. To explore and analyze the application effect of external and internal elevation of the maxillary sinus in implant restoration of the posterior maxilla. Methods. A total of 84 patients undergoing implant restoration of the posterior maxilla in the hospital were enrolled between January 2019 and March 2021. According to the random number table method, they were divided into the observation group (n = 42) and the control group (n = 42). The control group underwent external elevation of the maxillary s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 19 publications
(19 reference statements)
0
2
0
Order By: Relevance
“…There are multiple techniques and materials that can be employed depending on the case and dentist's preference. 21 In any case, one has to take some kind of precautionary step to avoid sinus complications. Limitation of this study was that the measurements were not correlated with history of respiratory diseases as they have an effect on the size of the sinuses.…”
Section: Discussionmentioning
confidence: 99%
“…There are multiple techniques and materials that can be employed depending on the case and dentist's preference. 21 In any case, one has to take some kind of precautionary step to avoid sinus complications. Limitation of this study was that the measurements were not correlated with history of respiratory diseases as they have an effect on the size of the sinuses.…”
Section: Discussionmentioning
confidence: 99%
“…Conforme relatam os estudos de Deng et al (2022) e Mello Neto, Ferreira Filho e Cordeiro (2023), uma das técnicas cirúrgicas comuns para elevação do seio maxilar é a Técnica da Janela Lateral, que tem sido amplamente reconhecida por sua segurança e eficácia na literatura. Esta técnica envolve a criação de uma janela óssea na parede lateral do seio maxilar para acessar e elevar a membrana sinusal.…”
Section: Public Medline or Publisher Medline (Pubmed) E Literatura La...unclassified
“…Este objetivo pode ser alcançado usando uma técnica de um ou dois estágios. A técnica de um estágio insere implantes dentários simultaneamente com o procedimento de aumento do seio maxilar (DENG et al, 2022;MELO NETO;FERREIRA FILHO;CORDEIRO, 2023). A membrana Schneideriana é uma membrana que forma o revestimento da face interna do seio maxilar.…”
Section: Introductionunclassified
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%